Women Workers at Sugarcane Mills at PT. Prima Alam Gemilang: A Study of Socialist Feminism - Hermina, Sitti; Laxmi, Laxmi; Aris, La Ode (International Journal of Artificial Intelligence Research, 2024)
The interest in working for a woman is influenced by various factors, one of which is the development of industry. Therefore, this article aims to find out the entry of women in Watu-Watu Lantari Jaya Village who are choosing to work at PT. Prima Alam Gemilang. Meanwhile, the data in this article were obtained through the method of observation involved, in-depth interviews corroborated with life history, then analyzed using the theory of Socialist Feminism by Heidi Hartman so as to answer the problems in this study as the results of the study show that women who work as employees at PT. Prima Alam Gemilang is a woman who works to strengthen family life. This condition can be interpreted as working as employees in the company can provide welfare to their families. In addition, there is an influx of women who work at PT in Watu-Watu Lantari Jaya Village. Prima Alam Gemilang, due to the various facilities provided for women, has a positive work environment in the company because the company prioritizes gender sensitivity and affirmative action for female workers.